Development of a Sustainable Composite Material Based on Rice Husk and Polystyrene - DOKO, KOUANDETÉ VALERY; Chabi, Edem; Amadji, Paul Damien; Gbian Tabe, Ahmed; Binjo, Bilali; Olodo, E.T. Emmanuel (My University, 2023)
The combination of rice husk and expanded polystyrene for the fabrication of sustainable composites is a direction that is not well-explored in scientific literature. In this context, this research focuses on the feasibility and physical properties of composites developed from these materials. The methodology encompasses a mechanical grinding process of rice husks, dissolution of polystyrene in an organic solvent to form a binder, and the fabrication of composites through cold compaction. The fabricated composites were analyzed for their physical properties, particularly density, mass loss after compaction and air storage, and their swelling upon immersion. Finegrained composites record a higher mass loss (13.17% for MF1 and 12.48% for MF2) compared to
Keywords: Bio-based materials; rice husk; expanded polystyrene; waste valorization; eco-material.